Lacunar infarction associated with anabolic steroids and polycythemia: a case report. - Harston, G; Batt, F; Fan, L; Okell, T; Sheerin, F; Littlewood, T; Kennedy, J (Karger Publishers, 2014)
Lacunar infarction is traditionally ascribed to lipohyalinosis or microatheroma. We report the case of 40-year-old man, without traditional risk factors for ischemic stroke, who presented to the Emergency Department with recurrent episodes of transient right-sided weakness and paresthesia. Lacunar infarction was confirmed on diffusion-weighted MRI and blood tests showed a marked polycythemia. Quantitative magnetic resonance perfusion imaging demonstrated dramatically abnormal perfusion throughout both cerebral hemispheres, and transcranial Doppler revealed reduced cerebral artery velocities, both consistent with the proposed mechanism of hyperviscosity. His symptoms settled with treatment of the polycythemia and workup did not find another cause of ischemic stroke. We propose that hyperviscosity secondary to steroid-induced polycythemia caused ischemia in this case and not lipohyalinosis or microatheroma, to which lacunar disease is commonly attributed.